Self-Assembled Hierarchical Formation of Conjugated 3D Cobalt Oxide Nanobead-CNT-Graphene Nanostructure Using Microwaves for High-Performance Supercapacitor Electrode - Kumar R.; Singh R.K.; Dubey P.K.; Singh D.P.; Yadav R.M. (My University, 2025)
Here we report the electrochemical performance of a interesting three-dimensional (3D) structures comprised of zero-dimensional (0D) cobalt oxide nanobeads, one-dimensional (1D) carbon nanotubes and two-dimensional (2D) graphene, stacked hierarchically. We have synthesized 3D self-assembled hierarchical nanostructure comprised of cobalt oxide nanobeads (Co-nb), carbon nanotubes (CNTs), and graphene nanosheets (GNSs) for high-performance supercapacitor electrode application. This 3D self-assembled hierarchical nanostructure Co3O4 nanobeads-CNTs-GNSs (3D:Co-nb@CG) is grown at a large scale (gram) through simple, facile, and ultrafast microwave irradiation (MWI). In 3D:Co-nb@CG nanostructure, Co3O4 nanobeads are attached to the CNT surfaces grown on GNSs. Our ultrafast, one-step approach not only renders simultaneous growth of cobalt oxide and CNTs on graphene nanosheets but also institutes the intrinsic dispersion of carbon nanotubes and cobalt oxide within a highly conductive scaffold. The 3D:Co-nb@CG electrode shows better electrochemical performance with a maximum specific capacitance of 600 F/g at the charge/discharge current density of 0.7A/g in KOH electrolyte, which is 1.56 times higher than that of Co3O4-decorated graphene (Co-np@G) nanostructure. This electrode also shows a long cyclic life, excellent rate capability, and high specific capacitance. It also shows high stability after few cycles (550 cycles) and exhibits high capacitance retention behavior. It was observed that the supercapacitor retained 94.5% of its initial capacitance even after 5000 cycles, indicating its excellent cyclic stability. The synergistic effect of the 3D:Co-nb@CG appears to contribute to the enhanced electrochemical performances. © 2015 American Chemical Society.